Preparedness to Teach: A Comparison Between Consecutive and Concurrent Education Students - Li, Xiaobin (Alberta Journal of Educational Research, 1999)
This study compared two groups of education students. One group consisted of students in a consecutive program, and the other consisted of students in a concurrent program. A survey that collected a sample of responses from 88 students in an Ontario faculty of education in the 1995-1996 academic year was analyzed quantitatively. The findings, contrary to some previous claims and present assumptions that concurrent students are better prepared than consecutive students, suggest that the combined effects of classroom instruction and practicum are sufficient to enable students enrolled in a consecutive program to develop feelings of preparedness to teach equivalent to those of the concurrent students. The results also suggest no significant difference in the number of self-reported classroom management and discipline problems encountered by the two groups during their practicum. Furthermore, the findings demonstrate a positive association between student teachers' feelings of preparedness to teach and their reported practicum classroom management experiences.